Pengaruh Model Conceptual Understanding Procedures Terhadap Penguasaan Konsep dan Kemampuan Pemecahan Masalah Fisika Peserta Didik Kelas X SMAN 1 Gerung - Nurul Hidayah; Hikmawati Hikmawati; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
Quasi experimental research with "non-equivalent control group design" aims to determine the effect of conceptual understanding procedures model on the mastery of concepts and ability to solve the physics problems of class X students SMAN 1 Gerung tahun 2017/2018. Population in this research is all students of class X MIPA SMAN 1 Gerung with sampling technique using purposive sampling, so selected class X MIPA 2 as experiment class and class X MIPA 5 as control class. Data collection of the mastery of concepts was performed using multiple choice test with mean score for experimental class of 72,96 and for control class equal to 63,29 and problem solving ability using essay test with mean value for experiment class was 56,30 and for the control class of 44.48. After the teaching, the mastery of the concepts of both classes increased, the second highest grade values occurred in the mechanical energy sub-material with the percentage of 69% in the experimental class and 66% in the control class whereas the second lowest grade occurred on the restoring force sub-material. Problem-solving abilities (PSAs) were 6 indicators, in the control class PSA-1 higher than the experimental class, while the PSA-2 through the PSA-6 experimental class was higher than the control class. The hypothesis of this study was tested by the test-t polled variance with a significant level of 5% and obtained t count of 4.65 for the mastery of concepts and t count of 3.50 for problem-solving abilities while the t table value of 1.99 means t count more great from t table. The results of this study indicate that there is influence conceptual understanding procedures model to the mastery of the concept and ability of solving physics problems of students class X SMAN 1 Gerung academic year 2017/2018.